Prevalence of involvement of the masseter and sternocleidomastoid muscles and relationship with the presence of vertigo in patients with craniocervicomandibular dysfunction between 2017 and 2021 (Research, Society and Development, 2023)
The American Association of Orofacial Pain defines temporomandibular disorders (TMD) as a set of disorders involving the temporomandibular joint (TMJ), masticatory muscles and associated structures. When these changes in the stomatognathic system are associated with impairment of the cervical muscles of contiguity, it is called craniocervicomandibular dysfunction (DCCM). Among the muscles involved, the sternocleidomastoid and masseter muscles are prevalent trigger points. Furthermore, a symptom that is routinely reported and present in the literature is vertigo associated with DCCM. The present work aims to survey the prevalence of involvement of the sternocleidomastoid and masseter muscles, as well as their relationship with vertigo in patients who suffer from temporomandibular disorders between the years 2017 to 2021, based on the medical records of the Clínica de Stomatologia da UEA Dental Polyclinic. The information collected from a reference health unit in the state is relevant to the scientific literature, contributing to the visibility of the importance of developing this type of research and thus helping to stimulate investments that improve the diagnosis and treatment of these craniocervicomandibular disorders.